Glucose turnover in the post-absorptive rat and the effects of halothane anaesthesia. - Heath, D; Frayn, K; Rose, J (1977)
1. Rates and rate coefficients of glucose utilization and replacement in post-absorptive rats, either conscious or under halothane anaesthesia, were determined in a thermoneutral environment by using [5-3H]- and [U-14C]glucose. Label was not injected into rats under halothane until about 0.5h after anaesthesia was initiated. 2. Comparison with the results for 24h-starved rats in the preceding paper [Heath et al. (1977) Biochem. J. 162, 643-651] showed that insulin concentrations were considerably higher but rate coefficients for glucose utilization were little altered in post-absorptive rats. Sensitivity to insulin was thus considerably increased by a 24h period of starvation in the rat. 3. Fractional recycling of glucose carbon in post-absorptive rats was under one-half of that in starved rats, reflecting the larger contribution of liver glycogenolysis to glucose production in the former. 4. In post-absorptive rats halothane decreased the mean rate of glucose utilization by about 17%. This decrease was associated with an increase in mean plasma insulin concentration, showing that halothane decreased sensitivity to insulin. 5. Recycling was slightly increased by halothane, indicating that the contribution of liver glycogen to the total glucogenic rate was decreased, probably because liver glycogen concentration were about 40% lower throughout the rate determinations in halothane. 6. Comparison of our results with earlier work shows that during and shortly after induction of halothane anaesthesia glucose turnover must have been greatly increased whereas from about 0.5h after induction it was decreased.